561. Co-occurring Psychosocial Barriers to Viral Suppression Among Men Who Have Sex with Men (MSM) in India. (26th November 2018) - Prabhu, Sandeep; Srikrishnan, Aylur Kailasam; Mehta, Shruti; McFall, Allison; Anand, Santhanam; Lucas, Gregory; Vasudevan, C K; Celentano, David; Solomon, Sunil
Abstract: Background: There is a paucity of data on factors associated with viral suppression in representative populations of HIV-positive MSM in low-middle income country (LMIC) settings. We characterized factors associated with viral suppression among a community-recruited sample of MSM across India with a particular focus on depression, alcohol use and recreational drug use. Methods: Of 10, 024 MSM recruited using respondent-driven sampling (RDS) from 10 Indian cities between August 2016 and April /2017, 1, 460 were HIV-positive and eligible for ART. Alcohol dependence was defined as AUDIT score ≥15; severe depression as PHQ-9 score ≥15; recreational drug use included both injection and non-injection use of drugs common in India, excluding marijuana. Prevalence ratios (aPrR) were obtained using multivariable Poisson regression incorporating RDS2 weights and accounting for clustering by site. Results: Median age was 37 years, 34.1% had at least high school education and 66.0% reported monthly income >115. Prevalence of viral suppression among HIV+ ART eligible MSM was 66.2% overall, ranging from 35.2% in Bhopal to 76.1% in Madurai with no regional trends. Prevalence of severe depression was 4.0%, alcohol dependence 66.3% and recreational drug use 9.5%. Viral suppression was significantly more common among those who were older and had higher treatment literacy. In analyses that adjusted for these factors and sexual identity, those who reported drug use and had evidence of severe depression had a significantly lower likelihood of being virally suppressed (aPrR 0.38; [95% CI: 0.16–0.89]) than those with neither ( P -value for interaction = 0.05). Similarly, compared with those who used neither alcohol nor drugs, those using both had a lower prevalence of viral suppression (aPrR: 0.61; [95% CI: 0.40–0.94]) although the interaction did not achieve statistical significance ( P = 0.07). Conclusion: In this population of MSM in an LMIC, recreational drug use appeared to be a key barrier to achieving viral suppression. Moreover, the impact of drug use was greater in the context of co-occurring severe depression or co-occurring alcohol dependence. It is critical that HIV programming in India and other resource-limited settings incorporate interventions to address these conditions in differentiated care models to maximize viral suppression. Disclosures: All authors: No reported disclosures.